Neuromechanics of finger hangs with arm lock-offs: analyzing joint moments and muscle activations to improve practice guidelines for climbing - Exel, J.; Deimel, D.; Koller, W.; Werle, C.; Baca, A.; Maffiodo, D.; Sesana, R.; Colombo, A.; Kainz, H. (Frontiers in Sports and Active Living, 2023)
Introduction: Climbing imposes substantial demands on the upper limbs and understanding the mechanical loads experienced by the joints during climbing movements is crucial for injury prevention and optimizing training protocols. This study aimed to quantify and compare upper limb joint loads and muscle activations during isometric finger hanging exercises with different arm lock-off positions.